Fertility preservation for female patients with childhood, adolescent, and young adult cancer: recommendations from the PanCareLIFE Consortium and the International Late Effects of Childhood Cancer Guideline Harmonization Group - Mulder, Renée L.; Font-Gonzalez, Anna; Hudson, Melissa M.; van Santen, Hanneke M.; Loeffen, Erik A.H.; Burns, Karen C.; Quinn, Gwendolyn P.; van Dulmen-den Broeder, Eline; Byrne, Julianne; Haupt, Riccardo; Wallace, W. Hamish; van den Heuvel-Eibrink, Marry M.; et al. (Lancet Oncology, 2021)
Female patients with childhood, adolescent, and young adult cancer are at increased risk for fertility impairment when treatment adversely affects the function of reproductive organs. Patients and their families desire biological children but substantial variations in clinical practice guidelines reduce consistent and timely implementation of effective interventions for fertility preservation across institutions. As part of the PanCareLIFE Consortium, and in collaboration with the International Late Effects of Childhood Cancer Guideline Harmonization Group, we reviewed the current literature and developed a clinical practice guideline for fertility preservation in female patients who were diagnosed with childhood, adolescent, and young adult cancer at age 25 years or younger, including guidance on risk assessment and available methods for fertility preservation. The Grading of Recommendations Assessment, Development and Evaluation methodology was used to grade the available evidence and to form the recommendations. This clinical practice guideline leverages existing evidence and international expertise to develop transparent recommendations that are easy to use to facilitate the care of female patients with childhood, adolescent, and young adult cancer who are at high risk for fertility impairment. A complete review of the existing evidence, including a quality assessment, transparent reporting of the guideline panel's decisions, and achievement of global interdisciplinary consensus, is an important result of this intensive collaboration.
CRIS-Team Scopus Importer:2021-02-12

Late Effects in Children and Adolescents with Osteosarcoma - Bielack, Stefan S.; Hecker-Nolting, Stefanie; Beck, Johannes (Springer International Publishing, 2020)
Multimodal osteosarcoma therapy according to past and current European and American protocols is described. This includes both local treatment (usually surgery) and systemic antineoplastic therapy, which is often based on high-dose methotrexate, doxorubicin (Adriamycin), cisplatin, and sometimes ifosfamide. As all must be employed at relatively high doses, early and late adverse effects have long been a major research focus. Their long-term late effects on organ function are described, and recommendations for lifelong follow-up are given. These are meant to comply with the evidence-based recommendations of the International Guideline Harmonization Group. Follow-up after surgery of the primary tumor and (endoprosthetic) reconstruction require the expertise of specialized centers.
CRIS-Team Scopus Importer:2024-12-16
Keywords: International Guideline Harmonization Group; Long-term late effects follow-up; Multimodal therapy; Osteosarcoma

Ototoxicity After Childhood Cancer - Tillmanns, Amélie; Lanvers-Kaminsky, Claudia; Parfitt, Ross; Meijer, Annelot; Tóth, Miklós; Münscher, Adrian; Beck, Johannes; van den Heuvel-Eibrink, Marry; am Zehnhoff-Dinnesen, Antoinette (Springer International Publishing, 2020)
Ototoxicity (i.e., toxic damage to the ear) is a side effect of many drugs that are used in cancer treatment, including anticancer drugs and co-medication such as aminoglycoside antibiotics, glycopeptide antibiotics, macrolides, nonsteroidal anti-inflammatory drugs, loop diuretics, ototopical medication, and cranial irradiation, among others. Aminoglycosides and platinum-based chemotherapy agents are of greatest concern as they often lead to permanent ototoxicity. Ototoxic drugs can have severe short- and long-term effects on patients’ hearing and balance systems, such as impaired speech perception, which impedes language development, psychosocial development, educational attainment, employment prospects, and quality of life. Oncology professionals must balance the benefits of any planned drug treatment against these potential effects. Susceptibility to ototoxic effects is defined by genetic and non-genetic risk factors, such as age or other concomitant ototoxic treatment. Various subjective and objective audiological tests can be used to identify ototoxicity in individual patients, such as pure-tone or play audiometry alongside otoacoustic emissions (OAEs) and auditory brainstem response (ABR) testing. The pros and cons of diagnostic audiological practice, treatment options, and current research into otoprotective medication are discussed in this chapter.
CRIS-Team Scopus Importer:2024-12-16

The impact of the temporal sequence of cranial radiotherapy and platin-based chemotherapy on hearing impairment in pediatric and adolescent CNS and head-and-neck cancer patients: A report from the PanCareLIFE consortium - Scobioala, Sergiu; Parfitt, Ross; Matulat, Peter; Byrne, Julianne; Langer, Thorsten; Troschel, Fabian M.; Hesping, Amélie E.; Clemens, Eva; Kaatsch, Peter; Grabow, Desiree; Kaiser, Melanie; Spix, Claudia; et al. (International Journal of Cancer, 2023)
The impact of the temporal sequence by which cranial radiotherapy (CRT) and platin-based chemotherapy (PCth) are administered on sensorineural hearing loss (SNHL) in pediatric and adolescent central nervous system (CNS) and head-and-neck (HN) cancer patients has not yet been studied in detail. We examined the ototoxic effects of sequentially applied CRT and PCth. This study included children and adolescents with CNS and HN tumors who participated in the multicountry PanCareLIFE (PCL) consortium. Audiological outcomes were compared between patients who received CRT prior to PCth and those who received it afterwards. The incidence, degree and posttreatment progression of SNHL, defined as Muenster classification grade ≥MS2b, were evaluated in 141 patients. One hundred and nineteen patients were included in a time-to-onset analysis. Eighty-eight patients received CRT prior to PCth (Group 1) and 53 patients received PCth before CRT (Group 2). Over a median follow-up time of 1.6 years, 72.7% of patients in Group 1 experienced SNHL ≥ MS2b compared to 33.9% in Group 2 (P <.01). A time-to-onset analysis was performed for 74 patients from Group 1 and 45 patients from Group 2. Median time to hearing loss (HL) ≥ MS2b was 1.2 years in Group 1 and 4.4 years in Group 2 (P <.01). Thus, audiological outcomes were better for patients who received CRT after PCth than before. This finding should be further evaluated and considered within clinical practice in order to minimize hearing loss in children and adolescents with CNS and HN tumors.
CRIS-Team Scopus Importer:2023-09-29
Keywords: cranial radiotherapy; PanCareLIFE project; platin-based chemotherapy; posttreatment hearing loss; therapy sequence